The Impact of Using Digital Books as A Media in Online Arabic Learning - Nurul Hamidah; Lailatul Mauludiyah; Abdul Haris (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This study aimed to analyse the process of using digital books to learn Arabic and its impact on online Arabic learning. The research was conducted at MTs Wahid Hasyim 01 Malang. This study took a qualitative approach and conducted case study research. An Arabic teacher and ten eighth-grade students from MTs. Wahid Hasyim and Malang served as research subjects. Data collection methods used are observation, interview, and documentary. The data analysis technique uses the Miles and Huberman interactive technique by going through the stages of data reduction, data display, and drawing conclusions. The results of the study show that the implementation of the utilisation is carried out through three stages of digital books by following the Ministry of Education and Culture's distance learning guidelines and taking scenario A through the processes of preparation, implementation, and evaluation. Students are of the view that using digital books makes them more interested in learning, helps them concentrate more, and can improve their learning outcomes.